Efektifitas Program KALIBER Sebagai Upaya Edukasi dan Preventif Bahaya Praktek Politik Uang Menjelang Pemilu 2024 - Ragil, Ragil; Qayyum, Habil Ildi; Bahari, Hizbul; Haskar, Edi (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2024)
Elections are a five-yearly democratic celebration that has a very important meaning in the life of the nation and state in Indonesia. The role of the community is very determining in the results of the 2024 election because with these results we, the Indonesian people, will show the world the quality of the implementation of democracy in this country. UMSB Law Faculty students in the form of the KALIBER (Kawal Pemilu Bersih) program are trying to play their role in guarding the 2024 elections in order to realize an election process that is clean and free from money politics. Through steps to provide information and educate the public about the dangers of money politics, as well as preventative efforts so that the public is not contaminated by these illegal practices in order to realize dignified elections. The aim of this program is to analyze the knowledge of prospective voters, both advanced voters and beginner voters, regarding the forms and methods of implementing money politics carried out by legislative candidates, election teams and election organizers. This research uses qualitative research methods of observation and interviews. The results of this research show that the KALIBER program can play an important role in realizing elections that are clean and free from money politics in order to realize dignified elections in 2024.